Diagnosis and Therapeutic Management of Trypanosoma evansi in an American Bully with Corneal Opacity - R Patel, Bhavika; Kumar, Binod; K Patbandha, Tapas; Vasava, Amrita; S Prajapati, Ankit (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Trypanosomosis is a haemoprotozoan infection, caused by different members of Trypanosoma species. It is widely dispersed form of animal trypanosomosis that is harmful, affecting various domestic and wild animal species (Eloy and Lucheis, 2009). Most of the time, the parasite is mechanically transmitted by biting flies like Tabanus, Stomoxes, Tsetse and Culicoides (Green, 2006). Canine trypanosomosis varies in severity from acute to subacute and chronic form. Dogs are frequently affected by an acute and severe form, which may result in death within two to four weeks (Soulsby, 1982). The clinical manifestations of canine trypanosomosis include weight loss, growing weakness, anorexia, anaemia, intermittent fever, conjunctivitis, swelling of the head, throat and limbs, staggering gait, enlarged superficial lymph nodes, difficulty in swallowing and corneal opacity due to strong reactions from the immune system (Kumar et al., 2020). One of the main symptoms of this condition is anaemia, which is caused by the mononuclear phagocytic system expelling red blood cells from the bloodstream. After an infection lasting several months, anaemia may recover to varying degrees when the parasitaemia becomes low and sporadic (Urquhart et al., 2002). The World Animal Health Organization currently classifies T. evansi as a multi-species illness and a zoonotic disease, following the clinical case reports of human trypanosomosis in Egypt and India (Aregawi et al., 2019). A single dose of diminazene aceturate is sufficient to eradicate a trypanosomosis infection in dog (Agrawal et al., 2020); however there are several more efficient trypanosomacidal medicines for dogs, such as suramin and quinapyramine (Rani and Suresh, 2007). Giving diminazene diaceturate to dogs at a dose rate higher than 3.5 mg/kg body weight is deemed lethal (Han et al., 2014). In India, the occurrence of canine trypanosomosis is sporadic in nature (Behera et al., 2017). However, no report on canine trypanosomosis with ophthalmic involvement has been reported in western India in particular Gujarat. Therefore, the present case report documents on the clinical presentations, diagnosis, haemato-biochemistry and therapeutic management of trypanosomosis in an American bully dog from Gujarat.